Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, a.a.a^2.a^4
=a^8
b, 4^3.2^4.2^5.16
=(2^2)^3.2^4.2^5.2^3
=2^6.2^4.2^5.2^3
=2^18
c, 5^2.5^3.125
=5^2.5^3.5^3
=5^8
d, 3^2.9.81
=3^2.3^2.3^4
=3^8
e, 2^3.2^3.18^2
=2^6.(2.3^2)^2
=2^6.2^2.3^4
=2^8.3^4
a)a.a.a^2.a^4 = a^2.a^2.a^4=a^8
b)4^3.2^4.2^5.16
=(2^2)^3.2^4.2^5.2^4
=2^6.2^4.2^4.2^4
=2^18
c)3^2.9.81
=3^2.3^2.3^4
=3^8
Ta có \(3.3^4.3=3^{1+4+1}=3^6\)
\(3.3.2^3.2.6=3.3.2^3.2.2.3=\left(3.3.3\right).\left(2^3.2.2\right)=3^3.2^5\)
\(2^3.2^4.2.8=2^3.2^4.2.2^4=2^{3+4+1+4}=2^{12}\)
\(a.a.a^2.a^3.a^4=a^{1+1+2+3+4}=a^{11}\)
\(x.y.x.y.x.y=x^3.y^3\)
\(3\cdot3^4\cdot3=3^6\)
\(3\cdot3\cdot2^3\cdot2\cdot6=3\cdot3\cdot2^3\cdot2\cdot3\cdot2=3^3\cdot2^5\)
\(2^3\cdot2^4\cdot2\cdot8=2^3\cdot2^4\cdot2\cdot2^3=2^{11}\)
\(a\cdot a\cdot a^2\cdot a^3\cdot a^4=a^{11}\)
\(x\cdot y\cdot x\cdot y\cdot x\cdot y=x^3y^3\)
a) \(3^3.4^2\)
b) \(a^3+a^4\)
c) \(5^2\)
d) \(\frac{3^6.5}{4^2}\)
e) \(\frac{3^4.9^4}{9^4}=3^4\)
GIẢI
1. (a.a + 2a.b + b.b )
= 2a + 2ab + 2b
= 2( a + ab + b )
2. a.a.a + b.b.b
= 3a + 3b
= 3( ab )
toán vớ vẩn cũng sai logic
1/2 ạ ông ơi